RF CMOS Power Amplifiers: Theory, Design and Implementation - Hella, Mona Mostafa; Ismail, Mohammed (The International Series in Engineering and Computer Science, Analog Circuits and Signal Processing, 2002)
RF CMOS Power Amplifiers: Theory Design and Implementation focuses on the design procedure and the testing issues of CMOS RF power amplifiers. This is the first monograph addressing RF CMOS power amplifier design for emerging wireless standards. The focus on power amplifiers for short is distance wireless personal and local area networks (PAN and LAN), however the design techniques are also applicable to emerging wide area networks (WAN) infrastructure using micro or pico cell networks. The book discusses CMOS power amplifier design principles and theory and describes the architectures and tardeoffs in designing linear and nonlinear power amplifiers. It then details design examples of RF CMOS power amplifiers for short distance wireless applications (e, g., Bluetooth, WLAN) including designs for multi-standard platforms. Design aspects of RF circuits in deep submicron CMOS are also discussed. RF CMOS Power Amplifiers: Theory Design and Implementation serves as a reference for RF IC design engineers and RD and R&D managers in industry, and for graduate students conducting research in wireless semiconductor IC design in general and with CMOS technology in particular